Pandemics and Power: An Applied Analysis of American Inequality - Megan A. Engle (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2022)
Pandemics represent both social change and continuance. While these public health crises bring about seemingly new issues, they also have a unique ability to reveal pre-existing problems within our society and perpetual social processes. Understanding historical patterns related to public health crises provides greater insight on the ongoing pandemic and American policy needs. Research reveals that, both historically and presently, systemic social injustices and economic inequalities are inflamed by such events. As a result, pandemics disproportionately affect minority groups in several interconnected ways. In examining public health theory, past pandemics, and the present moment, the effects of both power disparities and increased pressure on an already divided society become painfully apparent. I contend that in the digital age, the power structures underwriting our collective social response to public health crises are changing. With social and mass media providing minority groups a greater platform to vocalize their interests, we have seen an unprecedented push for progressive social change. As such, this pandemic represents an interesting perpetuation and deviation from historical public health crisis social response patterns.
Keywords: pandemics; public health; social response; social change; power